2015
DOI: 10.5812/jjhr.24720v2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Eight-Week Rope Skipping Exercise Program on Interleukin-10 and C-Reactive Protein in Overweight and Obese Adolescents

Abstract: Background: Patients often complain about the esthetic problems of gingival pigmentation. The aim of this study was to compare the effectiveness and recurrence of diode laser 810 nm and cryosurgery for gingival depigmentation. Methods: A total of 12 patients with physiologic gingival pigmentation were selected. The inclusion criterion was the presence of gingival pigmentation of maxillary incisors and the exclusion criteria was the presence of systemic diseases or use of any drugs associated with gingival pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The main source of pro-inflammatory cytokine secretion is adipose tissue. It has been reported that both JRE and dark chocolate supplementation reduces concentrations of pro-inflammatory cytokines [ 7 , 40 , 41 ]. For instance, Sung et al showed that 12 weeks of JRE decreased systemic inflammation by reducing hs-CRP concentrations in prehypertensive adolescent girls [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main source of pro-inflammatory cytokine secretion is adipose tissue. It has been reported that both JRE and dark chocolate supplementation reduces concentrations of pro-inflammatory cytokines [ 7 , 40 , 41 ]. For instance, Sung et al showed that 12 weeks of JRE decreased systemic inflammation by reducing hs-CRP concentrations in prehypertensive adolescent girls [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, anaerobic interval training significantly decreases CRP levels in male rats (Alizadeh et al 2015). Eight-week jumping rope interval training significantly decreases CRP levels and increases Interleukin-10 (IL-10) in obese and overweight adolescents (Zakavi et al 2015).…”
Section: Introductionmentioning
confidence: 99%